Study of Potential Drug-Drug Interactions in Prescriptions of University- Based Pharmacies - Sarah Mousavi; Molood Norouzi; Asieh Ashouri; MohammadReza Javadi; Kheirollah Gholami; Molouk Hadjibabaie (Research Center for Rational Use of Drugs (RCRUD), 2015)
Background: Drug-Drug Interactions (DDIs) are adverse reactions caused by a combination of drugs; they are often predictable and therefore avoidable or manageable. The objective of this study was to evaluate the nature, type and prevalence of potential DDIs in prescriptions dispensed in university-based community pharmacies in Tehran, Iran. Methods: From July 2012 to February 2014, sample of 1260 prescriptions were collected from community and outpatient hospital pharmacies affiliated to Tehran University of Medical Sciences (TUMS), Iran. The prescriptions were assessed using the reference text "drug interaction facts". The identified DDIs were categorized according to their level of significance into three classes (minor, moderate, major). Results: At least one drug-drug interaction was present in 339 (26.9%) of prescriptions and a total of 751 cases of interactions were found in prescriptions. Major DDIs represented 7.3% of all DDIs detected, whereas moderate DDIs were 75% of all DDIs. The mean number of drugs per prescriptions was 3.2, with a median of 4 (range, 2-10).There was a positive association between number of prescribed drugs and occurrence of DDIs (OR: 2.14, 95% CI: 1.9-2.4). The prescriptions of medical specialist had greater risk of occurrence of moderate severity DDIs than general practitioners (OR: 1.52, 95%CI: 1.08-2.15). Conclusion: Despite the prescriptions were collected from university-based pharmacies, but the overall prevalence of potential DDIs were high among patients. Physicians should be aware of potentially harmful DDIs. Meanwhile Pharmacists can contribute to the detection and prevention of drug-related injuries. Appropriate education, collaborating drug selection and pharmaceutical care are strongly recommended for physicians and pharmacists.